The ideology of terrorism as a tool of international political influence - Стадніченко, Р. В. (Proceedings of the Kyiv Aviation Institute. Series: Philosophy. Cultural, 2017)
The article is devoted to the study of one of the forms of terrorism manifestation - namely ideological. The focus of the study is a globalized world, where there is a continuous confrontation for spheres of influence through various doctrinal instruments. One of such tools, the ideology of the terrorist struggle is increasingly being implemented.